2020
DOI: 10.7554/elife.61174
|View full text |Cite
|
Sign up to set email alerts
|

The half-life of the bone-derived hormone osteocalcin is regulated through O-glycosylation in mice, but not in humans

Abstract: Osteocalcin (OCN) is an osteoblast-derived hormone with pleiotropic physiological functions. Like many peptide hormones, OCN is subjected to post-translational modifications (PTMs) which control its activity. Here, we uncover O-glycosylation as a novel PTM present on mouse OCN and occurring on a single serine (S8) independently of its carboxylation and endoproteolysis, two other PTMs regulating this hormone. We also show that O-glycosylation increases OCN half-life in plasma ex vivo and in the circulation in v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Yet, probably the most critical consequence of the identification of Gprc6a as a receptor of osteocalcin has been to allow the study of the biology of osteocalcin in humans as will be described below. More broadly, it gave to osteocalcin a more complete hormonal identity, which has now been confirmed by numerous independent cell culture studies, in vivo studies in multiple species and multiple disease models, by correlative studies in humans and as we will describe, human genetic evidence [37,42,45–120]. It was also confirmed even more recently by the generation of a new genetic model of Osteocalcin deficiency [50].…”
Section: The Foreseen Functions Of Osteocalcinmentioning
confidence: 78%
See 1 more Smart Citation
“…Yet, probably the most critical consequence of the identification of Gprc6a as a receptor of osteocalcin has been to allow the study of the biology of osteocalcin in humans as will be described below. More broadly, it gave to osteocalcin a more complete hormonal identity, which has now been confirmed by numerous independent cell culture studies, in vivo studies in multiple species and multiple disease models, by correlative studies in humans and as we will describe, human genetic evidence [37,42,45–120]. It was also confirmed even more recently by the generation of a new genetic model of Osteocalcin deficiency [50].…”
Section: The Foreseen Functions Of Osteocalcinmentioning
confidence: 78%
“…It was also confirmed even more recently by the generation of a new genetic model of Osteocalcin deficiency [50]. While the evidence indicating that osteocalcin acts as a hormone in rodents and primates grows at an increasing pace, as the sample of references presented above indicates [37,42,45–120], this does not mean that there are no studies in which Osteocalcin ‐deficient mice were presented as normal [51].…”
Section: The Foreseen Functions Of Osteocalcinmentioning
confidence: 99%
“…Recently, an interesting study published in eLife uncovered a novel O-glycosylation modification on a single serine (S8) of mouse OCN, which is essential to increase the stability of OCN in circulation, while the human OCN (hOCN) cannot be O-glycosylated as the corresponding amino acid residue is a tyrosine (Y12). 4 Moreover, they demonstrated that a single-point mutation (Y12S) is sufficient to mediate the O-glycosylate and then increase the half-life of hOCN ex vivo . These findings provide an explanation of the differences in circulation levels of OCN between humans and mice.…”
Section: Challenges Of Osteokine Clinical Transformationmentioning
confidence: 99%
“…Osteocalcin is a noncollagenous protein secreted by osteoblasts, reflecting osteoblast activity [ 11 ]. Interestingly, osteocalcin knockout mice are characterized by an increase in visceral fat mass, as well as hyperglycemia, hypoinsulinemia, and reduced β-cell mass [ 12 ], indicating that osteocalcin regulates glucose metabolism and insulin secretion in mice [ 13 , 14 , 15 ]. Furthermore, administration of osteocalcin was shown to improve insulin sensitivity and to decrease the severity of obesity and T2DM in mice fed with a high-fat diet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%